ChemInform Abstract: Base‐Mediated Regiospecific Cascade Synthesis of N‐(2‐Pyridyl)pyrroles from N‐Propargylic β‐Enaminones. Issue 40 (September 2016) - Shen, Jinhai; Yang, Xifa; Wang, Fuyuan; Wang, Yue; Cheng, Guolin; Cui, Xiuling
Abstract: The pyrrole and pyridine rings are installed simultaneously under KOH‐mediated mild reaction conditions.